The role of adipocyte-specific IL-6-type cytokine signaling in FFA and leptin release. (3rd July 2018) - Wueest, Stephan; Konrad, Daniel
ABSTRACT: High secretion of interleukin (IL)-6 from white adipose tissue may contribute to metabolic complications in obesity. We have recently shown that IL-6-type cytokine signaling in adipocytes is involved in the development of obesity-associated hepatic insulin resistance and steatosis. In addition, we revealed that adipocyte-specific IL-6 signaling ameliorates glucose metabolism in obesity via enhancing insulin secretion. Mechanistically, IL-6 induces the release of free fatty acid (FFA) and leptin from adipocytes thereby affecting liver metabolism and pancreatic β-cell function, respectively. This commentary further discusses the role of adipocyte-specific IL-6-type cytokine signaling in the regulation of FFA and leptin release. In particular, we outline depot-specific differences in IL-6-induced basal release of the two aforementioned factors. Moreover, we provide evidence that insulin's effect on the release of FFA and leptin is adipose depot-dependent. We conclude that adipose depot-specific targeting of the IL-6 signaling pathway may be a novel approach to blunt obesity-associated metabolic complications.